2013
DOI: 10.1111/acem.12161
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Ultrasound in the Diagnosis of Appendicitis in Children in a Multicenter Cohort

Abstract: Objectives The objectives were to assess the test characteristics of ultrasound (US) in diagnosing appendicitis in children and to evaluate site-related variations based on the frequency of its use. Additionally, the authors assessed the test characteristics of US when the appendix was clearly visualized. Methods This was a secondary analysis of a prospective, 10-center observational study. Children aged 3 to 18 years with acute abdominal pain concerning for appendicitis were enrolled. US was performed at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
99
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(112 citation statements)
references
References 30 publications
(51 reference statements)
10
99
0
3
Order By: Relevance
“…[40][41][42][43] Our study had a high rate of equivocal US that was comparable to that found in our recent study of appendicitis 9 and higher than that reported in a multisite study by Bachur et al 44 who found a 14% equivocal US rate. This difference may be in part explained by the difference in the criteria for equivocal US.…”
Section: Discussionsupporting
confidence: 85%
“…[40][41][42][43] Our study had a high rate of equivocal US that was comparable to that found in our recent study of appendicitis 9 and higher than that reported in a multisite study by Bachur et al 44 who found a 14% equivocal US rate. This difference may be in part explained by the difference in the criteria for equivocal US.…”
Section: Discussionsupporting
confidence: 85%
“…16 Consequently, a substantial proportion of paediatric appendicitis cases may be misdiagnosed if clinical decision making is based on physical examination, symptoms and laboratory investigations alone. 17 To prevent misdiagnosis and reduce negative appendectomy rates, imaging has been recommended as part of the diagnostic pathway. 16 Ultrasound (US) is generally the diagnostic imaging modality of choice where paediatric appendicitis is suspected as it is: readily available; has no radiation risk; is relatively fast; and, in comparison to other cross-sectional imaging modalities, is relatively inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…However, complete visualization of the appendix using US has recently been reported to range from 25% to 73%, leaving the clinician with a significant diagnostic conundrum. 13 The objective of this study was to determine outcomes in children with suspected appendicitis who have incompletely visualized appendices on US. We also examined the frequency of incomplete visualization, the diagnostic accuracy of US when the appendix is visualized, and the predictive value of secondary signs of inflammation when the appendix is not visualized.…”
mentioning
confidence: 99%